Preference learning versus coherent arbitrariness: NOAA guidelines or a learning design contingent valuation (LDCV) - Ian J. Bateman; Diane Burgess; W. George Hutchinson; David I. Matthews (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2006)
We extend the contingent valuation (CV) method to test three differing conceptions of individuals' preferences as either: (i) a-priori well-formed or readily divined and revealed through a single dichotomous choice question (as per the NOAA CV guidelines; Arrow et al., 1993]; (ii) learned or 'discovered' through a process of repetition and experience [Plott, 1996; List, 2003]; (iii) internally coherent but strongly influenced by some initial arbitrary anchor [Ariely et al., 2003]. Findings reject both the first and last of these conceptions in favour of a model in which preferences converge towards standard expectations through a process of repetition and learning.
Keywords: D6; D12; Q51; C51; Q18; 330; coherent arbitrariness; Contingent valuation; discovered preferences; learning; Preference formation